B10 Inclusion formation in mutant HTT exon 1 expressing human neuronal cells. (13th September 2016) - Ghosh, Rhia; Wood-Kaczmar, Alison; Andre, Ralph; Kriston-Vizi, Janos; Ketteler, Robin; Cole, Sarah; Smith, Edward J; Bates, Gillian P; Tabrizi, Sarah J
Abstract : Background: Neuronal inclusion formation is a pathognomonic feature of Huntington's disease (HD). Recent evidence has suggested that these inclusion bodies (IBs) may comprise a heterogeneous population of huntingtin (HTT) protein species, a subset of which may lead to impaired cell viability and ultimately cell death. Aim: To investigate the formation of inclusions in human neurons derived from neural stem cells (NSCs) (ReNcell VM) stably transduced to over-express HTT exon 1 fragments with either normal (29Q) or pathogenic polyglutamine tracts (71 Q and 129Q). Methods: High-content screening of neurons stained with anti-HTT antibody S830 was carried out using a Perkin Elmer Opera LX confocal microscope. Subsequent quantitative image analysis was carried out using ImageJ and R. Individual cells were analysed in more detail using super resolution imaging (N-SIM Super Resolution System). The effect of mHTT exon 1 on neuronal viability was assessed using a variety of biochemical techniques (LDH assay, MTT and Alamar Blue). Results: Inclusion bodies form in a small proportion of (1%) of neurons, and are predominantly intra-nuclear, though a lower proportion of cells display smaller perinuclear inclusions. The formation of nuclear inclusions increases in a polyQ- length dependent manner and over time. Super resolution microscopy of individual cells has demonstrated this to be an all-or-nothing phenomenon. A diffuse cytosolic form of mHTT also accumulates in the cells over time. There is no overt effect on basal viability in these mHTT exon 1 expressing neurons. Conclusions: We have characterised the spatio-temporal profile of mHTT inclusion formation in mHTT expressing NSCs and neurons, and have demonstrated poly-Q and time-dependent accumulation of IBs. A deeper understanding of relationship between the different forms of mHTT and neuronal vulnerability is essential for the design of targeted therapeutics.